A case of Ehlers–Danlos syndrome presenting with widened atrophic scars of forehead, elbow, knee, and pretibial area: A case report. Issue 37 (September 2019) - Xu, Xiangwen; Wang, Zhichao; Zan, Tao
Abstract: Rational: Ehlers–Danlos syndrome (EDS) is a heritable connective tissue disorder. Currently, the genotype-phenotype correlations of classical EDS (cEDS) are still controversial. Hence, this study reported a case of cEDS with both clinical manifestations and COL5A2 gene mutation. Patient concerns: A 30-year-old female presented to the plastic-surgery clinic with widen atrophic scars on forehead, elbows, knees and pretibial area that had developed since childhood. Diagnosis: With the skin hyperextensibility, joint hypermobility, papyraceous scar revealed by physical examination, and the heterozygous pathogenic variant c1997G > A (p.P659P) in COL5A2 gene revealed by whole exome sequencing, the diagnosis of the classical Ehlers–Danlos syndrome was made. Interventions: The patient underwent facial scar resection and sutured in minimizing tension and perfect apposition to avoid the post-surgery scar formation. Outcomes: Follow-up 6 months after surgery, the wound remained a fine line scar. Lessons: Our findings suggested that COL5A2 gene mutation (c1997G > A p.P659P) may be associated with cEDS but did not reveal other severe complications.